Orbital mesenchymal chondrosarcoma: a case report - Qian Luo; Shuai Wu (Journal of International Medical Research)
Extraskeletal orbital mesenchymal chondrosarcoma is an extremely rare and highly aggressive tumor. We herein report a case involving a woman in her early 20s diagnosed with orbital mesenchymal chondrosarcoma. This case report aims to increase recognition and understanding of this condition.